Experimental Games for Strengthening Collective Action? Learning from Field Experiments in India - International Food Policy Research Institute; Arizona State University; Foundation for Ecological Security; Jana Jagrithi (International Food Policy Research Institute, 2018)
Groundwater is a common pool resource which experiences depletion in many places around the world. The increased use of irrigation and water demanding cash crops stimulate this development. This project aims to test whether experimental games can only be used to measure collective action but also to strengthen collective action for managing shared natural resources (groundwater) in Andhra Pradesh, India. Two NGOs (Foundation for Ecological Security and Jana Jagriti) ran the games in communities in which they were working to improve watershed and water management. The game looks at how people make decisions in what crops to plant. Games were played with groups of five men or five women, followed by a community debriefing. Two different payment methods (flat-fee for a community fund or individual payments) were used to test whether the payment method affects behavior and the way people play the games. Behavioral and attitudinal variables regarding water use and mechanisms for regulating and responding to changes and uncertainty in social and ecological conditions were also monitored at the household and community levels. Treatment groups were villages in which field experiments with collective action games were implemented. Control cases were comparable communities where no such experiments were conducted but the same NGOs are working to strengthen collective groundwater management. Follow up game sessions and surveys were conducted two years after the initial sessions to explore any lasting effect, if any, of such intervention. The game protocol was slightly modified in the second wave to incorporate domestic water consumption in the game scenario. Overall, this project analyses whether the experimental exercise changes participants’ mental models about the interactions between resource dynamics, group goals, and private interests.